Clinical Decision Support Improves Adherence to Pediatric Antimicrobial Renal Dosing Guidelines - Quach, Andrew; Ateya, Mohammad B.; Zimmerman, Christopher (ACI Open, 2018)
Background Antimicrobial drug dosage selection requires consideration of patient demographics, renal function, and indication(s) of use. We developed a strategy that employed upfront passive dose-guidance clinical decision support (CDS) in addition to noninterruptive/interruptive maximum dose warnings to guide providers to order renally appropriate antimicrobial drug therapy.Objectives Our objective was to assess the impact of passive dose-guidance CDS, along with a successive CDS strategy that provided renal dosing assistance at multiple points throughout order entry, on provider adherence to pediatric antimicrobial dosing guidelines.Methods A single-center, observational, retrospective cohort study at an academic pediatric hospital. The study compared the proportion of orders adherent to the institutional guidelines across three time points: a historical control (October 2014 to March 2015), phase I implementation (March 2015 to May 2015), and phase II implementation (May 2015 to October 2015).Results The proportion of adherent orders with respect to dose and frequency was 74% in the control period, 76% (odds ratio [OR] = 1.11; 95% confidence interval [CI], 0.76–1.16, p = 0.6) in phase I of the study, and increased to 81% (OR = 1.54; 95% CI, 1.16–2.03, p = 0.003) in phase II of the study.Conclusion Provider adherence to institutional antimicrobial dosing guidelines improved following the implementation of a successive CDS combining passive and noninterruptive/interruptive approaches. This study displays the value of designing CDS that occurs at multiple points within ordering workflow and minimizes intrusiveness. Our CDS strategy can be considered for implementation by other institutions using similar electronic health record systems.
Keywords: computerized provider order entry; clinical decision support; electronic health record; renal dose adjustment; medication alert systems